Electrical impedance myography in facioscapulohumeral muscular dystrophy: A 1‐year follow‐up study. Issue 2 (17th April 2018) - Mul, Karlien; Heatwole, Chad; Eichinger, Katy; Dilek, Nuran; Martens, William B.; Van Engelen, Baziel G. M.; Tawil, Rabi; Statland, Jeffrey M.
ABSTRACT: Introduction : Electrical impedance myography (EIM) is a noninvasive technique for measuring muscle composition and a potential physiological biomarker for facioscapulohumeral muscular dystrophy (FSHD). Methods : Thirty‐two participants with genetically confirmed and clinically affected FSHD underwent EIM in 7 muscles bilaterally. Correlations between EIM and baseline clinical measures were used to select EIM variables of interest in FSHD, and EIM and clinical measures were followed for 1 year. Results : There were no significant changes in the EIM variables. Although 50‐kHZ reactance correlated the strongest with clinical measures at baseline, the 50–211‐kHZ phase ratio demonstrated lower within‐subject 12‐month variability, potentially offering sample size savings for FSHD clinical trial planning. Discussion : EIM did not identify significant disease progression over 12 months. It is currently unclear whether this is because of limitations of the technology or the slow rate of disease progression in this cohort of FSHD patients over this period of time. Muscle Nerve 58 : 213–218, 2018